Nesfatin-1 Acts Centrally to Induce Sympathetic Activation of Brown Adipose Tissue and Non-Shivering Thermogenesis - Levata, Luka; Dore, Riccardo; Jöhren, Olaf; Schwaninger, Markus; Schulz, Carla; Lehnert, Hendrik (Hormone and Metabolic Research, 2019)
Nesfatin-1 has originally been established as a bioactive peptide interacting with key hypothalamic nuclei and neural circuitries in control of feeding behavior, while its effect on energy expenditure has only recently been investigated. Hence, the aim of this study was to examine whether centrally acting nesfatin-1 can induce β3-adrenergic stimulation, which is a prerequisite for the activation of thermogenic genes and heat release from interscapular brown adipose tissue, key physiological features that underlie increased energy expenditure. This question was addressed in non-fasted mice stereotactically cannulated to receive nesfatin-1 intracerebroventricularly together with peripheral injection of the β3-adrenoceptor antagonist SR 59230 A, to assess whole-body energy metabolism. Using a minimally invasive thermography technique, we now demonstrate that the thermogenic effect of an anorectic nesfatin-1 dose critically depends on β3 adrenergic stimulation, as the co-administration with SR 59230 A completely abolished heat production from interscapular brown adipose tissue and rise in ocular surface temperature, thus preventing body weight loss. Moreover, through indirect calorimetry it could be shown that the anorectic concentration of nesfatin-1 augments overall caloric expenditure. Plausibly, central administration of nesfatin-1 also enhanced the expression of DIO2 and CIDEA mRNA in brown adipose tissue critically involved in the regulation of thermogenesis.
Keywords: β-adrenoceptors; thermogenesis; SR 59230 A; caloric expenditure